Effects of atractylodin and β-Eudesmol on P-glycoprotein and Caco-2 cells permeability - Artitaya Thiengsusuk; Wiriyaporn Sumsakul; Kesara Na-Bangchang (Elsevier, 2025)
Background: Atractylodin and β-eudesmol are the major constituents of Atractylodes lancea (Thunb.) D.C. (AL) which have been demonstrated potential activities against cholangiocarcinoma in a series of in vitro and in vivo studies. Purpose: The study investigated their membrane permeability properties and effects on the efflux transporter P-glycoprotein (P-gp) using a Caco-2 cell monolayer. Methods: The transport and modulatory effects of both compounds on the expression of MDR-1 mRNA and protein, including P-gp function were investigated using the Caco-2 cells, RT-PCR, western blot analysis, and Rhodamine 123 (R123) assay, respectively. Results: The efflux ratio of atractylodin and β-eudesmol (50-200 µM) was higher than 2, indicating the predominant efflux transport of both compounds compared with the influx transport. However, neither of the compounds were P-gp inhibitors nor modulators of the expression of MDR-1 mRNA, and P-gp function. Only a slight inhibitory effect was observed with atractylodin exposure at 160 µM for 24 hrs. Conclusion: The low permeability of both compounds across the Caco-2 cell monolayer in both directions may lead to inadequate concentrations in the target cells, which may limit the clinical use of AL in cholangiocarcinoma treatment. Concurrent administration of both compounds and substrates of P-gp is not a clinical concern since neither compound is an inhibitor of P-gp in Caco-2 monolayers.